Analisis Kinerja Di Upt Pjj Bina Marga Provinsi Di Kota Malang - Handoko, Waskito Dwi; Nyuherno, Nyuherno; Setyowati, Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this research is to identify the Application of Capability Analysis at UPT Maintenance of Provincial Line Bridges in Malang Malang City. The results of this research prove that: (1) in the usual way the maintenance of the Malang City route has been carried out but it is still not optimal and there are still many obstacles in its implementation. As a result, the expected results have not been fully successful, (2) Based on the results in the square, the powerful factors that limit the achievement of goals are at least the resources of the people they have, the management of the duration of the accounting year which does not integrate with the situation in the square. But behind that, some residents thought that the local authorities had shown a fairly optimal response in maintaining the roads in Malang City. It is also the support of the residents that is the impetus for local authorities.